Creatinine to Cystatin C Ratio, a Biomarker of Sarcopenia Measures and Falls Risk in Community-Dwelling Older Women. Issue 7 (15th December 2021) - Sim, Marc; Dalla Via, Jack; Scott, David; Lim, Wai H; Hodgson, Jonathan M; Zhu, Kun; Daly, Robin M; Duque, Gustavo; Prince, Richard L; Lewis, Joshua R
Abstract: Background: The ratio of creatinine to cystatin C (Cr:Cyc) has been proposed as a biomarker of sarcopenia, as greater Cr:Cyc is typically associated with greater muscle mass. We examined the relationship between Cr:Cyc with individual sarcopenia measures, 5-year self-reported falls, and 12-year fall-related hospitalizations in a prospective cohort study of 1 118 community-dwelling older women (mean age 75.2 ± 2.7 years). Methods: Serum Cr:Cyc, hand grip strength, and timed-up-and-go performance were assessed at baseline (1998), while dual-energy x-ray absorptiometry-derived appendicular lean mass (ALM)/height 2 (m) was obtained in a subset of women at baseline and 1 year ( n = 334). Incident 5-year self-reported falls and 12-year falls-related hospitalizations were considered. Results: In a multivariable-adjusted model, women with the lowest Cr:Cyc (Quartile [Q] 1) had 5% (1.0 kg) weaker grip strength, as well as 3.7% (0.22 kg/m 2 ) and 5.5% (0.031) lower ALM adjusted for height 2 or body mass index, respectively, compared to women in Q4 (all p < .05). 329 women reported an incident fall over 5 years, and 326 fall-related hospitalizations were recorded over 12 years. Women in Q1 of Cr:Cyc had a greater relative hazard for a fall over 5 years (hazard ratio [HR] 1.50; 95% confidence interval [CI] 1.11–2.01) and fall-related hospitalization over 12 years (HR 1.53; 95% CI 1.13–2.07) compared to Q4 in the multivariable-adjusted model. Conclusion: These findings support further investigation into the use of Cr:Cyc as a muscle biomarker to help clinicians identify individuals at risk of falls for early inclusion into evidence-based primary prevention programs targeting improvements to diet and exercise.